Serial blood lactate levels as a prognostic factor for sepsis mortality - Keswari Aji Patriawati; Nurnaningsih Nurnaningsih; Purnomo Suryantoro (Indonesian Pediatric Society Publishing House, 2014)
Background Sepsis is a major health problem in children and a leading cause of death. In recent decades, lactate has been studied as a biomarker for sepsis, and as an indicator of global tissue hypoxia, increased glycolysis, endotoxin effect, and anaerobic metabolism. Many studies h ave shown both high levels and increased serial blood lactate level measurements to be associated with increased risk of sepsis mortality. Objective To evaluate serial blood lactate levels as a prognostic factor for sepsis mortality. Methods We performed an observational, prospective study in the Pediatric Intensive Care Unit (PICU) at DR. Sardjito Hospital, Yogyakarta from July to November 2012. We collected serial blood lactate specimens of children with sepsis, first at the time of admission, followed by 6 and 24 hours later. The outcome measure was mortality at the end ofintensive care. Relative risks and 95% confidence intervals of the factors associated with mortality were calculated using univariate and multivariate analyses. Results Sepsis was found in 91 (50.3%) patients admitted to the PIW , of whom 75 were included in this study. Five patients (6. 7%) died before the 24-hour lactate collection and 39 patients (52.0%) died during the study. Blood lactate levels of ~ 4mmol;L at the first and 24-hour specimens were associated with mortality (RR 2.9; 95%CI 1.09 to 7 .66 and RR 4.92; 95%CI 1.77 to 13.65, respectively). Lactate clearance of less than 10% at 24 hours (adjusted RR 5.3; 95% CI 1.1 to 24.5) had a significantly greater risk fo llowed by septic shock (adjusted RR 1.54; 95%CI 1.36 to 6.4 7) due to mortality. Conclusion In children with sepsis there is a greater risk of mortality in those with increasing or persistently high serial blood lactate levels, as shown by less than 10% lactate clearance at 24-hours after PIW admission.